Pro‐ and anti‐inflammatory cytokine gene single‐nucleotide polymorphisms in inflammatory bowel disease. (31st October 2014) - López‐Hernández, R.; Valdés, M.; Campillo, J. A.; Martínez‐García, P.; Salama, H.; Bolarin, J. M.; Martínez, H.; Moya‐Quiles, M. R.; Minguela, A.; Sánchez‐Torres, A.; Botella, C.; Salgado, G.; et al.
Summary Anti‐inflammatory cytokines have an important role in disease, tumour and transplant processes. Alterations in the regulation of several cytokines have been implicated in a variety of inflammatory disorders, including IBD (inflammatory bowel disease) [Crohn′s disease (CD) and ulcerative colitis (UC)]. Cytokine polymorphisms are also known to affect the level of gene expression. Thus, the aim of this study was to determine the relationship between cytokine polymorphisms and the IBD pathologies in a Spanish population. Polymorphisms analysis was performed using PCR‐SSOP using a microbeads luminex assay. The following polymorphisms were determined: TNFα [−238G/A (rs361525) and −308G/A (rs1800629)], IFNγ [+874A/T (rs62559044)], TGFβ [+869C/T (rs1982073) and +915G/C (rs1800471)], IL10 [−1082A/A (rs1800896), −592A/C (rs1800872), −819C/T (rs1800871)], IL6 [−174C/G (rs1800795)], IL12p40 [3′UTR −1188A/C (rs3212227)], IL1α [−889C/T (rs1800587)], IL1β [−511C/T (rs1143634) and +3962C/T (rs1143633)], IL1R [Pst‐1 1970C/T] and IL1RA [Mspa‐1 11100C/T]. No statistical differences in TNFα, IFNγ, TGFβ, IL10, IL6, IL1α, IL1β, IL1R and IL1Ra genotypes and allele distributions between the IBD groups and healthy controls were found. However, we observed significant differences in the 3′UTR −1188A/C polymorphism of IL12p40. So −1188A allele was increased in patients with UC and the −1188C allele (high IL12p40 production) was increased in patients with CD with respect to controls. These data are in concordance with the fact that CD has been shown to be associated with a Th1 T‐cell‐mediated inflammation model and high IL12/IFNγ production at histological affected sites. These data suggest that cytokine polymorphisms in TNFα, IFNγ, TGFβ, IL10, IL6 and IL1α, IL1β, IL1R and IL1Ra cytokine gene do not seem to be relevant in IBD susceptibility and IL12p40 3′UTR −1188A/C polymorphism seems to be associated with a differential IBD development.